(untitled) (Research, Society and Development, 2024)
The increasing use of biomarkers in different medical specialties has shown promise in personalizing the diagnosis and treatment of several pathologies. Given this relevance, this article proposes to conduct a narrative bibliographic review, with the aim of presenting and discussing clinical cases developed by the authors that exemplify the application of biomarkers in the clinical context. Through the analysis of multiple studies, we seek to synthesize current knowledge, identify gaps and provide a comprehensive view of the role of biomarkers in medical practice. This review is of special interest to health professionals and researchers seeking to deepen their understanding of the subject, contributing to the advancement of knowledge in the area. The keywords were colitis, cancer, exams, clinical and biomarkers. Biomarkers, also known as biological markers, are experimentally measurable indicators that signal the occurrence of a normal or pathological function in an organism or the response to a pharmacological agent. These biomarkers can be of different types, such as physiological (organ functions), physical (characteristic changes in biological structures), histological (tissue samples obtained by biopsy) and anatomical. They can include specific cells, molecules, genes, enzymes or hormones. Among the most relevant in medical research are biochemical markers, which can be obtained relatively easily from body fluids, facilitating the work of researchers. In clinical practice, biomarkers are used for diagnosis, identification of disease risks, patient stratification and assessment of the severity or progression of a condition. In addition, they are useful for predicting prognoses and monitoring treatments, reducing the likelihood of side effects. In some cases, biomarkers also serve as auxiliary tools for regulatory entities to make decisions about drug approval.